On the Phase Relationship between Excitatory and Inhibitory Neurons in Oscillation - Zou, Xiaolong; Wang, Da-Hui (Frontiers in Computational Neuroscience, 2016)
Characteristic phase shifts between discharges of pyramidal cells and interneurons in oscillation have been widely observed in experiments, and they have been suggested to play important roles in neural computation. Previous studies mainly explored two independent mechanisms to generate neural oscillation, one is based on the interaction loop between pyramidal cells and interneurons, referred to as the E-I loop, and the other is based on the interaction loop between interneurons, referred to as the I-I loop. In the present study, we consider neural networks consisting of both the E-I and I-I loops, and the network oscillation can operate under either E-I loop dominating mode or I-I loop dominating mode, depending on the network structure and neuronal connection patterns. We found that the phase shift between pyramidal cells and interneurons displays different characteristics in different oscillation modes, and its amplitude varies with the network parameters. We expect that this study helps us to understand the structural characteristics of neural circuits underlying various oscillation behaviors observed in experiments.